Pengaruh Tenaga Kerja dan Investasi Terhadap PDRB Subsektor Ekonomi Kreatif Kota Surabaya - Rakhadita, Anisah Citra; Prabowo, P.S (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
This study aims to determine the effect of labor and investment on the GDRP of the creative economy sub-sector of Surabaya. Descriptive quantitative analysis and panel data regression analysis were used in this study. The data needed in this study are the distribution of GDRP, the percentage of labor, investment in the creative economy sub-sector of the City of Surabaya in the 2011-2019 period. The result of this study is that partially the labor has a significant and negative influence on the creative economy sub-sector, then the investment variable partially also shows a significant and negative influence on the GDRP of the creative economy sub-sector in Surabaya. Simultaneous test results in this study stated that the two independent variables had a significant and positive influence on the dependent variable, namely the GDRP of the creative economy sub-sector.